2013
DOI: 10.1039/c3ra41394b
|View full text |Cite
|
Sign up to set email alerts
|

One-step preparation of magnetic Janus particles using controlled phase separation of polymer blends and nanoparticles

Abstract: We present a simple method with the aid of a microfluidic droplet-generation technique to fabricate magnetic Janus particles by utilizing a solvent evaporation-induced phase separation and preferential partitioning of magnetic nanoparticles in the polymer blends. Non-aqueous emulsion droplets of the polymer blends and nanoparticles solution are produced to become Janus particles after the evaporation of the solvent. The stabilizing polymer of the nanoparticles, which is compatible only with one of the polymer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
54
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(54 citation statements)
references
References 58 publications
0
54
0
Order By: Relevance
“…This technique avoids the limits of the minimum biphasic droplet size and the problem of a blurred boundary by convective stirring across the interface within the biphasic droplets. Jeong et al reported a simple technique using the generation of droplets from a microfluidic device to prepare magnetic JPs through a combination of a solvent evaporation‐induced precipitation and biased segregation of magnetic nanoparticles in polymer blends . Oil‐based polymer blend emulsion droplets and nanoparticle solutions coalesced to form JPs after solvent evaporation.…”
Section: Techniques Of Fabricating Magnetic Jpsmentioning
confidence: 99%
“…This technique avoids the limits of the minimum biphasic droplet size and the problem of a blurred boundary by convective stirring across the interface within the biphasic droplets. Jeong et al reported a simple technique using the generation of droplets from a microfluidic device to prepare magnetic JPs through a combination of a solvent evaporation‐induced precipitation and biased segregation of magnetic nanoparticles in polymer blends . Oil‐based polymer blend emulsion droplets and nanoparticle solutions coalesced to form JPs after solvent evaporation.…”
Section: Techniques Of Fabricating Magnetic Jpsmentioning
confidence: 99%
“…The encapsulated magnetic nanoparticles have a broad range of applications in molecular and cellular biology, including miniaturized bioassays, immunoassays, cell separation, activation, and isolation of nucleic acids . Moreover, the addition of geometric and/or chemical anisotropies to such magnetic materials enables fine control of motion and orientation of a single particle as well as the reversible formation of directed assembly structures steered by an external field …”
Section: Introductionmentioning
confidence: 99%
“…Jeong et al presented the fabrication of magnetic Janus particles using solvent evaporation–triggered phase separation and preferential partitioning of magnetic nanoparticles in polymer blends. Upon applying an external magnetic field, the magnetic Janus particles formed straight chain‐like structures or zigzag strips depending on their morphological properties . Wang et al synthesized dumbbell‐ and snowman‐shaped magnetic particles via a combination of diffusion‐induced phase separation and the magnetically driven dewetting method .…”
Section: Introductionmentioning
confidence: 99%
“…For example, droplet‐based microfluidics enables the production of monodisperse biodegradable microspheres, which provide enhanced control over release rate with reduced initial burst . Uniform microcarriers with multiple compartments can also be created by phase separation of polymers in droplets to encapsulate and release multiple drugs . Alternatively, distinct laminar streams can be emulsified to form multiphasic particles .…”
Section: Introductionmentioning
confidence: 99%